The intraday interest rate: What's that? - Puriya Abbassi; Falko Fecht; Johannes Tischer (Deutsche Bundesbank, 2015)
We study the intraday interest rate in a CCP-based GC pooling repo market and its key determinants. Since collateral used in this market is identical to collateral eligible for the daylight overdraft facility of the Eurosystem, any intraday rate in this market cannot be a result of collateral constraints keeping banks from using the overdraft for arbitrage. Nevertheless, we find that in the crisis period a statistically and economically significant intraday spread (up to 60 basis points) prevailed that was only somewhat mitigated by the ECB's unconventional monetary policy measures. Our results show that this spread was mainly determined by the market liquidity of the repo market, suggesting that the intraday spread is largely a liquidity premium.
Keywords: E43; E50; G01; G10; G21; 330; intraday interest rate; central counterparty; overnight repos; central bank intervention; financial crisis